Repeating flaring activity of the blazar AO 0235+164 - Escudero Pedrosa, J.; Agudo, I.; Tramacere, A.; Marscher, A. P.; Jorstad, S.; Weaver, Z. R.; Casadio, C.; Thum, C.; Myserlis, I.; Fuentes, A.; Traianou, E.; Kim, J.-Y.; et al. (Astronomy and astrophysics (Berlin), 2024)
Context. Blazar AO 0235+164 , located at a redshift of z = 0.94, has undergone several sharp multi-spectral-range flaring episodes over recent decades. In particular, the episodes that peaked in 2008 and 2015, which were subject to extensive multi-wavelength coverage, exhibited an interesting behavior. Aims. We study the actual origin of these two observed flares by constraining the properties of the observed photo-polarimetric variability as well as of the broadband spectral energy distribution and the observed time-evolution behavior of the source. We use ultra-high-resolution total-flux and polarimetric very-long-baseline interferometry (VLBI) imaging. Methods. The analysis of VLBI images allowed us to constrain kinematic and geometrical parameters of the 7 mm jet. We used the discrete correlation function to compute the statistical correlation and the delays between emission at different spectral ranges. The multi-epoch modeling of the spectral energy distributions allowed us to propose specific models of the emission; in particular, with the aim to model the unusual spectral features observed in this source in the X-ray region of the spectrum during strong multi spectral-range flares. Results. We find that these X-ray spectral features can be explained by an emission component originating in a separate particle distribution than the one responsible for the two standard blazar bumps. This is in agreement with the results of our correlation analysis, where we did not find a strong correlation between the X-ray and the remaining spectral ranges. We find that both external Compton-dominated and synchrotron self-Compton-dominated models are able to explain the observed spectral energy distributions. However, the synchrotron self-Compton models are strongly favored by the delays and geometrical parameters inferred from the observations.